The potential applications of artificially modified exosomes derived from mesenchymal stem cells in tumor therapy - Song, Yilin; Song, Quanlin; Hu, Daosheng; Sun, Binwen; Gao, Mingwei; Liang, Xiangnan; Qu, Boxin; Suo, Lida; Yin, Zeli; Wang, Liming (Frontiers in Oncology, 2024)
Mesenchymal stem cells (MSCs) have tumor-homing ability and play critical roles in tumor treatment, but their dual influences on tumor progression limit their therapeutic applications.Exosomes derived from MSCs (MSC-exosomes) exhibit great potential in targeted tumor treatment due to their advantages of high stability, low immunogenicity, good biocompatibility, long circulation time and homing characteristics. Furthermore, the artificial modification of MSCexosomes could amplify their advantages and their inhibitory effect on tumors and could overcome the limit of tumor-promoting effect. In this review, we summarize the latest therapeutic strategies This is a provisional file, not the final typeset article involving artificially modified MSC-exosomes in tumor treatment, including employing these exosomes as nanomaterials to carry noncoding RNAs or their inhibitors and anticancer drugs, and genetic engineering modification of MSC-exosomes. We also discuss the feasibility of utilizing artificially modified MSC-exosomes as an emerging cell-free method for tumor treatment and related challenges.